2016
DOI: 10.1016/j.mayocp.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

New Insulin Delivery Recommendations

Abstract: Many primary care professionals manage injection or infusion therapies in patients with diabetes. Few published guidelines have been available to help such professionals and their patients manage these therapies. Herein, we present new, practical, and comprehensive recommendations for diabetes injections and infusions. These recommendations were informed by a large international survey of current practice and were written and vetted by 183 diabetes experts from 54 countries at the Forum for Injection Technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
278
0
30

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 234 publications
(324 citation statements)
references
References 214 publications
(150 reference statements)
2
278
0
30
Order By: Relevance
“…Those who always injected into an area of LH decreased with increasing age from 40.8 (G1) to 14.9 (G2) to 8.8% (G3). More than one-half of pediatric patients in every group reported having injection pain [5], with the younger the patients, the higher the percentage of those who reported pain, and the more frequently it was reported (Table 4). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who always injected into an area of LH decreased with increasing age from 40.8 (G1) to 14.9 (G2) to 8.8% (G3). More than one-half of pediatric patients in every group reported having injection pain [5], with the younger the patients, the higher the percentage of those who reported pain, and the more frequently it was reported (Table 4). …”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, the New Insulin Delivery Recommendations state that the 4-mm pen needle ‘should be considered the safest pen needles for adults and children regardless of age, gender, ethnicity and BMI’ [5]. The Recommendations also provide advice on site care, injection site rotation, prevention of complications, alleviation of pain, disposal of used sharps, and the appropriate psychological approach to managing pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive evidencebased guidelines are available to inform the correct injection technique. 10 Insulin technique counseling needs to be incorporated in every clinic visit.…”
Section: Methods Of Injectionmentioning
confidence: 99%
“…His injection practices revealed that he was self-administering insulin over the abdomen with the syringe of needle size 6 mm, apparently leading to intramuscular injection in a thin-built person 1. Furthermore, he was drawing his recommended dose of basal insulin with the 40 IU/mL syringe out of a vial of 100 IU/mL strength resulting into 2.5 times of the prescribed amount.…”
Section: Descriptionmentioning
confidence: 99%